Land Limitations and Institutional Adaptation in Early Childhood Education - Sri Nazwa; Topan Iskandar; Oyeronke Christiana Paramole (Early Childhood Development Gazette, 2025)
This study examines the impact of land limitations on the learning ecosystem, educational infrastructure capacity, and institutional adaptive strategies at Raudhatul Athfal. Employing a qualitative case study design, data were collected through direct observations and semi-structured interviews with the head of the institution, teachers, parents, and students. The findings reveal that spatial constraints significantly restrict children’s movement space, reduce the variation of learning activities—particularly gross motor activities—increase classroom density, and limit the availability and functionality of educational facilities and infrastructure. Overcrowded classrooms and shared use of specialized rooms affect instructional effectiveness, scheduling, and student comfort. However, the study also identifies adaptive institutional responses, including multifunctional classroom design, rotational scheduling of space usage, the use of portable and flexible learning media, vertical space optimization, and collaboration with the surrounding community to access alternative learning spaces. The study concludes that educational quality in spatially constrained environments depends not solely on physical infrastructure but on institutional resilience and adaptive capacity. Future research is recommended to employ mixed-method and comparative multi-site designs to quantitatively assess the long-term impact of spatial constraints on children’s developmental outcomes and learning achievement.